2009
DOI: 10.1007/978-0-387-77064-2_23
|View full text |Cite
|
Sign up to set email alerts
|

Motor Learning: Changes in the Structure of Variability in a Redundant Task

Abstract: Although variability is a fundamental and ubiquitous feature of movement in all biological systems, skilled performance is typically associated with a low level of variability and, implicitly, random noise. Hence, during practice performance variability undergoes changes leading to an overall reduction. However, learning manifests itself through more than just a reduction of random noise. To better understand the processes underlying acquisition and control of movements we show how the examination of variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
97
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(105 citation statements)
references
References 17 publications
(27 reference statements)
3
97
0
1
Order By: Relevance
“…Therefore, during practice, motor performance undergoes changes that lead to an overall reduction of trial-to-trial variability. 17,18 Although global coordination improved linearly throughout both stages of learning, it was only in the second phase that learners reached values approaching those of experts. 5 These data clearly indicate, however, that global coordination is not totally mastered by the end of the academic training.…”
Section: Motor Learning Principlesmentioning
confidence: 94%
“…Therefore, during practice, motor performance undergoes changes that lead to an overall reduction of trial-to-trial variability. 17,18 Although global coordination improved linearly throughout both stages of learning, it was only in the second phase that learners reached values approaching those of experts. 5 These data clearly indicate, however, that global coordination is not totally mastered by the end of the academic training.…”
Section: Motor Learning Principlesmentioning
confidence: 94%
“…Generalization developed along with a reduction of motion in those degrees of freedom not contributing to cursor motion (i.e., the task's null space). As recognized by Todorov and colleagues (Todorov 2004;Todorov and Jordan 2002) and others (Diedrichsen 2007;Latash et al 2007;Müller and Sternad 2009;Scheidt et al 2000;Scholz and Schöner 1999;Smith et al 2006), examining the evolution of behavior within the null space of the task provides insight into how the nervous system organizes and reorganizes patterns of coordination as it learns. In Mosier's study, reduction in the extent and variability of null-space motion may have reflected a minimization of task energetics or an optimization of some other measure of efficiency, an interpretation consistent with the view that motor planning and control can be understood as resulting from an interplay between competing kinematic, energetic, and/or other "costs of control" (Shadmehr and Krakauer 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that movement of all components in the system to constrain CoM movement [25] is achieved through a whole body synergy whereby movement of all constituent parts are related to each other. Movement variability of the constituent parts to some extent can cancel each other out so that an overall control parameter moves with reduced variability [21]. This co-variation or compensatory variability [26] during whole body movement has been demonstrated in a number of studies involving healthy subjects [25,[27][28].…”
mentioning
confidence: 87%
“…Variability is equally considered part of normal movement and is considered to be essential for effective motor control and motor learning [19][20]; for instance better coordination has been associated with reduced magnitudes of movement fluctuations [21]. It is unlikely that minimizing frontal plane knee movement is principally the parameter that is controlled during normal functional movement.…”
mentioning
confidence: 99%